Cinchona alkaloids are in extensive uses, not only for drugs but also for soft drink industries. They are harvested from the bark of trees Cinchona spp. after certain ages and therefore are available over a limited time. Cell culture is an alternative way to continuously produce such secondary metabolites in a much shorter time. Various substances were added in the normal growth media to promote quinoline alkaloids production by cell cultures of Cinchona ledgeriana. At the sixth week of culture, - DIAH RATNADEWI; . SUMARYONO (Bogor Agricultural University, Indonesia, 2010)
Cinchona alkaloids are in extensive uses, not only for drugs but also for soft drink industries. They are harvested from the bark of trees Cinchona spp. after certain ages and therefore are available over a limited time. Cell culture is an alternative way to continuously produce such secondary metabolites in a much shorter time. Various substances were added in the normal growth media to promote quinoline alkaloids production by cell cultures of Cinchona ledgeriana. At the sixth week of culture, quinine and cinchonine contents were suppressed by paclobutrazol (PBZ), abscisic acid (ABA), or even by precursor tryptophan, while cinchonidine content was enhanced by 0.2 mg/l tryptophan to 43 fold of that produced by untreated cells (2.8% dry weight). At the seventh week of culture, the production of quinine and quinidine started to grow whereas the production of cinchonine and cinchonidine tended to decrease. An addition of 5 mg/l PBZ to culture media yielded the highest level of total quinine/quinidine after seven weeks, e.g. quinine 11 times more abundant and quinidine 23 fold higher compared to the untreated cells. Particularly the level of quinine which is the most demanded for medical and industrial purposes still need to be improved to approach to or even higher than that of extracted from the conventional source.